SARS-CoV-2 inhibits induction of the MHC class I pathway by targeting the STAT1-IRF1-NLRC5 axis - Ji-Seung Yoo (Nature Portfolio, 2021)
The presentation of viral antigens to T cells via the MHC molecules is a critical component of the host response to viral infection. Here the authors suggest SARS-CoV-2 possesses the immune evasion strategy against the MHC class I pathway by targeting key transcriptional regulators.